ANALYSIS OF FACTORS INFLUENCING THE ACCOUNTABILITY OF VILLAGE FUNDS MANAGEMENT - R. Budi Hendaris; Rahmat Siraz (Dinasti International Journal of Education Management And Social Science, 2020)
To achieve a good village fund management, the necessary accountability village fund. Accountability is needed to explain the management of village funds. As a form of responsibility for the management of this fund, created the financial statements of the village. This study aimed to analyze whether the competence of human resources, the implementation of village financial system, and the implementation of internal control systems of government affect the accountability of village funds management . This research is descriptive and causal using survey by distributing questionnaires to the respondents who have been determined. The respondents totaled 160 respondents who are fund managers villages in West Bandung regency. For data analysis, this study uses PLS SEM assisted by Smart PLS software program version 3.0.